2008
DOI: 10.1152/jn.00020.2008
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Appropriate Locomotive Motor Output Through Interlimb Neural Pathway Within Spinal Cord in Humans

Abstract: Direct evidence supporting the contribution of upper limb motion on the generation of locomotive motor output in humans is still limited. Here, we aimed to examine the effect of upper limb motion on locomotor-like muscle activities in the lower limb in persons with spinal cord injury (SCI). By imposing passive locomotion-like leg movements, all cervical incomplete (n = 7) and thoracic complete SCI subjects (n = 5) exhibited locomotor-like muscle activity in their paralyzed soleus muscles. Upper limb movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 42 publications
3
57
2
Order By: Relevance
“…Previous studies have shown effects of rhythmic arm movements on lower limb muscle activation [10,11]. It is possible that the changes in muscle activation observed in the current study were partly caused by altered transmission in propriospinal neural pathways when arm movements were performed [27,28].…”
Section: Muscle Activity During Swingmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous studies have shown effects of rhythmic arm movements on lower limb muscle activation [10,11]. It is possible that the changes in muscle activation observed in the current study were partly caused by altered transmission in propriospinal neural pathways when arm movements were performed [27,28].…”
Section: Muscle Activity During Swingmentioning
confidence: 63%
“…Constraining the arms influences the gait pattern in both healthy [4][5][6] and patient [7,8] populations, and there is indirect support for the existence of coupling between upper and lower limb muscular activation patterns [5,9]. Accordingly, upper limb involvement altered lower limb muscle activation during recumbent stepping movements in healthy individuals [10] and during passive reciprocal leg movement in individuals with spinal cord injury [11]. While there are anecdotal reports from spinal cord injured patients that stepping was facilitated [12] and patterns of lower limb muscle activity improved [13] when arm swing was performed during walking, this has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Results from animal experiments (Grillner 1975) and human reflex and coordination studies (Kawashima et al 2008;Zehr et al 2004), as well as treadmill and overground locomotion (Ivanenko et al 2005), discuss the muscular control for both the upper and lower limbs as a consequence of central pattern generator activity. In accordance, a wider data set (i.e., including upper limb and trunk muscles) with respect to a previous study (Clark et al 2010) did not influence the number of motor modules needed for an accurate reconstruction of surface EMG patterns for both controls and stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only using the arms for postural and weight-bearing activity (e.g., on parallel bars or handrails), as is commonly applied in traditional locomotor rehabilitation, may actually inhibit rhythmic stepping with the legs [25]. Conversely, when arm activity is facilitated with locomotor-like arm and leg movements in those with incomplete cervical spinal cord injury, leg muscle activity is facilitated [26]. Allowing a normal simultaneous and reciprocating arm action may facilitate stepping and may be an important component needed to harness neural coupling to help improve motor output for the legs during walking [23,27].…”
Section: Introductionmentioning
confidence: 99%